Kritik atas Pandangan Theodor Noldeke tentang al-HurÃ»f al-Muqattaâah dalam al-Qurâan - Cholily, Naufal (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
The Holy Book of Koran have secrets contained in the al-hurÃ»f al-muqattaâah the letter opener. Not a few scholars who claim that al-hurÃ»f al-muqattaâah including part of paragraph mutashÃ¢bihÃ¢t meaning known only to God. However, many Muslim scholars or Orientalists who try to uncover secrets about the intentions of al-hurÃ»f al-muqattaâah. Among orientalists who participated in the secrets behind al-hurÃ»f al-muqattaâah is Theodor Noldeke. In his book, Geschichte des Qorans, Noldeke view that al-hurÃ»f al-muqattaâah not part of the Koran. Noldeke assume that al-hurÃ»f al-muqattaâah who are in the early surah is the initials of the names of the authors of the Koran. The initials have been used prior to the codification process in the future âUthmÃ¢n. the letter also as a symbol mushaf their disposal. For example Alif-LÃ¢m-RÃ¢ are the initials of al-Zubayr, the letter SÃ¢d for Hafsah, KÃ¢f to AbÃ» Bakr, and NÃ»n to âUthmÃ¢n. This paper will attempt to explore and criticize opinions Noldeke in more depth